Perilaku Seks Pranikah Pada Kalangan Remaja Di Kota Serang - Rodiyatul Awaliyah (Jurnal al-Shifa Bimbingan Konseling Islam, 2021)
ABSTRACT Premarital sexual behavior is sexual activity or behavior that involves two people who like or love each other and do it before marriage.. The research objective is to see and understand the description of premarital sex behavior among adolescents grouped in Serang City, with whom and where adolescents are having premarital sex, knowing how much influence the knowledge of premarital sex has, seeing the factors that cause premarital sex behavior in the adolescent class in Serang City, looks at the impact of premarital sex behavior on Serang City teenagers, and provides alternative solutions to tackle premarital sex behavior among adolescents in Serang City. This study uses a qualitative approach with a case research method. Determination of informants in this study using purposive sampling method. The research arrangement was carried out in Serang City. Methods of data in in-depth interviews, observation, documentation, and questionnaires. The data validity test was conducted by using the triangulation method of sources and member checks. The data analysis technique used is an interactive model consisting of data reduction, data display (data display), and conclusion drawing. The results showed that premarital sex behavior among adolescents in Serang City was mostly done but not openly in certain places such as boarding houses in Serang City and free. The factors that cause premarital sexual behavior are relationship with parents, religious education in the family, peers, and technology. Alternative guidance and counseling that can be given by counselors is counseling services with a Behavioral approach or with a rational emotive therapy (RET) approach. Keywords: premarital sex behavior, premarital sex factors, impact of premarital, counselling